Biocontrol and Mycotoxin Mitigation: An Endophytic Fungus from Maize Exhibiting Dual Antagonism Against Fusarium verticillioides and Fumonisin Reduction - Qianhui Li; Dongbeng Zhang; Dongyan Ye; Shuo Zhang; Qiurui Ma; Helong Bai; Fanlei Meng (Journal of Fungi)
Fusarium verticillioides is one of the pathogenic fungi causing maize ear rot, and its secreted fumonisins accumulated in plants pose significant threats to human health. To reduce the incidence of maize ear rot and fumonisin contamination, this study isolated numerous endophytic fungi from maize plants. Through inhibition zone and dual culture assays, an endophytic fungal strain, FJ284, demonstrating notable antifungal activity against F. verticillioides was screened. 18S rDNA gene sequencing was employed for fungal identification, and the sequences were deposited in NCBI GenBank. FJ284 was identified as Penicillium oxalicum. The ethyl acetate extract of P. oxalicum was analyzed using gas chromatography–mass spectrometry (GC-MS), revealing 52 compounds, including several secondary metabolites with documented anticancer, antimicrobial, and antioxidant activities. Furthermore, a spectroscopic method was developed to assess the inhibitory effect of strain FJ284 against F. verticillioides, showing maximum inhibition at 48 h. Finally, Ultra-High-Performance Liquid Chromatography–Mass Spectrometry (UHPLC-MS) analyses confirmed that FJ284 significantly inhibited three fumonisins (suppression rates > 50%), with efficacy ranked as fumonisin B3 (FB3) > fumonisin B2 (FB2) > fumonisin B1 (FB1).